Peran Kelompok Tani terhadap Peningkatan Produksi Padi Sawah di Desa Puundombi Kecamatan Tongauna Utara Kabupaten Konawe - Edi Susilo; Sarty Syarbiah; I Made Sukratman (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
To analyze the role of farmer groups in increasing the production of paddy farming in Puundombi Village, Tongauna Utara District, Konawe Regency. The number of samples in this study was 19 people. Taken 10-15% or 20-25% or more of the population. The Farmer Group Role Assessment Score was measured using a Likert scale. Each criterion has a range as a limit, the respondent's answers to each variable can be classified, namely (1) High Category, (2) Medium Category, (1) Low Category. The role of the paddy farming group in Puundombi Village, Tongauna Utara District, obtained the results of the role of the farmer group